Destrin Contributes to Lung Adenocarcinoma Progression by Activating Wnt/β-Catenin Signaling Pathway - Zhang, Hui-Juan; Chang, Wen-Jing; Jia, Cai-Yun; Qiao, Ling; Zhou, Jing; Chen, Qing; Zheng, Xiao-Wei; Zhang, Jian-Hua; Li, Hong-Chao; Yang, Zheng-Yan; Liu, Zhong-Hua; Liu, Guang-Chao; et al. (Molecular cancer research, 2020)
Lung cancer, especially lung adenocarcinoma, is one of the most common neoplasms worldwide. However, the mechanisms underlying its initiation, development, and metastasis are still poorly understood. Destrin (DSTN) is a member of ADF/cofilin family. Its detailed biological function remains unknown, although it is reported that DSTN is involved in cytoskeleton remodeling and regulation of actin filament turnover. Recent evidence has shown that high expression of cofilin-1 is associated with invasion and poor prognosis of several types of human tumors, but the detailed mechanism is still entirely unclear, particularly in lung cancer tumorigenesis and malignancy. Here, we report that DSTN was highly expressed in a mouse lung cancer model induced by urethane and in clinical lung adenocarcinoma tissue samples. Its expression level was positively correlated with cancer development, as well as metastasis to the liver and lymph nodes. Consistently, it was directly associated with the poor prognosis of lung adenocarcinoma patients. Furthermore, we also found that DSTN promotes cell proliferation, invasion, and migration , and facilitates subcutaneous tumor formation and lung metastasis via intravenous injection . Mechanically, DSTN associates with and facilitates nuclear translocation of β-catenin, which promotes epithelial-to-mesenchymal transition (EMT). Taken together, our results indicated that DSTN enhances lung cancer malignancy through facilitating β-catenin nuclear translocation and inducing EMT. Combined with multivariate analyses, DSTN might potentially serve as a therapeutic target and an independent prognostic marker of lung adenocarcinoma. IMPLICATIONS: This finding indicates that DSTN facilitates β-catenin nuclear translocation and promotes malignancy in lung adenocarcinoma.